Gene Therapy in Hemophilia: Clinical Trials Update - White, Gilbert C., II (Thrombosis and Haemostasis, 2001)
Disorders caused by inborn genetic errors have been a primary target for treatment by gene transfer. Hemophilia A and B have been considered especially important targets because the genes for factor VIII and IX are well characterized, levels of factor VIII and IX do not require complex regulation, small increases in factor level would have significant clinical benefits, good clinical and laboratory tests of efficacy exist, and excellent animal models of hemophilia are available. Four clinical trials of gene transfer in hemophilia, two in hemophilia A and two in hemophilia B, are currently underway or have been completed and two other trials have been approved. The collective interim results from these trials indicate that the current approaches and doses are safe and that low levels of expression are detected. These studies support the continued development of gene transfer as a potential treatment option for hemophilia.
Keywords: Hemophilia; gene therapy; retrovirus; adeno-associated virus; adenovirus